4t(-7t+19)=0

Simple and best practice solution for 4t(-7t+19)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4t(-7t+19)=0 equation:



4t(-7t+19)=0
We multiply parentheses
-28t^2+76t=0
a = -28; b = 76; c = 0;
Δ = b2-4ac
Δ = 762-4·(-28)·0
Δ = 5776
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$t_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$t_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{5776}=76$
$t_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(76)-76}{2*-28}=\frac{-152}{-56} =2+5/7 $
$t_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(76)+76}{2*-28}=\frac{0}{-56} =0 $

See similar equations:

| 8(5+x)=6x+52 | | 3(5x+-8)=36 | | 2s+s=9 | | -12x+4=12x+4 | | u/2-14=29 | | 30/x=5/100 | | 2(x+4)=3x+7 | | 2/4x+1=19 | | k-3/5=-4 | | =8x+1,275 | | 6x+8=10+6x | | 2(2n+2.4)=6.4 | | 30=x2+12 | | 1/3a+3=7 | | 12j−4j=8 | | m/8+6=32 | | 3x−9=45−6x | | x-2+2×+4+2×-2=180 | | x-3/10=1 | | 3(x+5)^2=48 | | 14y=16-4y | | h+6.5=−6.5 | | -9+6b=105 | | 31-8x=13+10x | | 0=(1200-100x)(10+2x) | | 18=-6/7h | | 35,000=x+19,000 | | 3(x-7)+4x=43 | | 2x+x+5-6=x | | -1+k/4=-2 | | 4n(8n+6)=0 | | 3x-14=x+16 |

Equations solver categories